The Tropological Animal: Beyond the Body and the Sovereign - Liponik, Vesna (Filozofski vestnik, 2023)
Biopolitics and necropolitics have used animals as a concept to illustrate a particular human biopolitical situation, much in the “tradition” of Aristotle’s provisional biopolitics. In the Western context, not only our understanding of politics but also tropology and the conceptual apparatus itself are haunted by this ancient legacy, which underlies a vertical ontology tied to processes of spatialization and containment, a vertical ontology that enables an intelligibility of figurative translation. The article considers tropological systems as systems embedded in particular forms of governmentality, forms of the violent administration of life and death. To show how certain bodies are marked as animal or animal-like and used in the (metaphorical) processes of exclusion/inclusion, it focuses on Giorgio Agamben’s thoughts on Carolus Linnaeus and Zakiyyah Iman Jackson’s analysis of metaphorics in the most recent (r)evolutionary theory, symbiogenesis, developed by Lynn Margulis. Moreover, to radically disturb the graduated ontological premises of traditional stylistics and tropology, we move beyond existing conceptualizations of the body and the sovereign, all of which are based on de-borderization, intersections, movements, and transfigurations.